Binary Ni2P/Ti3C2 multilayer cocatalyst anchored TiO2 nanocomposite with etchant/oxidation grown TiO2 NPs for enhancing photocatalytic H2 production - Muhammad Tahir, Muhammad Tahir (American Chemical Society, 2021)
Ternary nickel phosphide (Ni2P) and titanium carbide (Ti2C2) MXene supported titanium dioxide nanoparticles (TiO2 NPs) to construct a Ni2P/TiO2 NPs/Ti3C2 MXene hybrid composite for stimulating photocatalytic hydrogen production has been investigated. The performance comparison of two-dimensional (2D) Ti3C2 MXene multilayers with in situ grown TiO2 NPs synthesized through etching and atmospheric calcination methods was conducted and promising separation of charge carriers was observed. TiO2 NPs embedded over 2D Ti3C2, synthesized through both methods, were found to have promise in promoting photoactivity, whereas 2.89 times more H2 yield was attained with TiO2 NPs embedded through the oxidation (ox) approach. Using the Ni2P/TiO2/Ti3C2-ox heterostructure, a rate of 9425 ppm g-1 h-1 of H2 was reached, 2.77, 4.81, and 8.28 times more than those using Ni2P/TiO2, TiO2/Ti3C2 and TiO2 samples, respectively. This obviously augmented H2 production rate can be ascribed to a binary cocatalyst with efficient charge carrier separation, higher light absorption, and more attachment of water molecules. Among different alcohols, glycerol was a promising reagent to yield more hydrogen in addition to having higher photostability in consecutive cycles. This study provides a new approach to construct a ternary nanocomposite with proficient charge carrier separation and would be beneficial for other energy applications.